1982
DOI: 10.1111/j.1432-1033.1982.tb07036.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preferred Conformation of Oligosaccharides Derived from the Complex‐Type Carbohydrate Portions of Glycoproteins

Abstract: The preferred conformation in aqueous solution of oligosaccharides related to the complex-type carbohydrate portion of glycoproteins has been inferred from high-resolution nuclear magnetic resonance data (both ' H and I3C) combined with hard-sphere exo-anomeric calculations. The results indicate that the N-acetyl-lactosamine units are arranged in such a way that they are widely separated in space. Thus, these carbohydrates can cover large surface areas of the attached protein and provide good targets for recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 24 publications
4
28
0
1
Order By: Relevance
“…Through the acquisition of a 1 H-13 C HMBC spectrum, we were able to elucidate the interglycosidic linkage pattern, and we also confirmed that the glycan is O linked to the pilin peptide fragments via C1 of ␣Araf. In support of our structural characterization of the glycan, the 13 C chemical shift assignments for the ␣Araf units closely match values that have been previously reported for this monosaccharide (5).…”
Section: Pa5196 Pilins Are Modified With a Novel Glycan That Is Not Tsupporting
confidence: 71%
“…Through the acquisition of a 1 H-13 C HMBC spectrum, we were able to elucidate the interglycosidic linkage pattern, and we also confirmed that the glycan is O linked to the pilin peptide fragments via C1 of ␣Araf. In support of our structural characterization of the glycan, the 13 C chemical shift assignments for the ␣Araf units closely match values that have been previously reported for this monosaccharide (5).…”
Section: Pa5196 Pilins Are Modified With a Novel Glycan That Is Not Tsupporting
confidence: 71%
“…These minima are also consistent with previous calculations for this linkage that did not implicitly consider flexibility (26)(27)(28)(29). In two crystal structures of small molecules with this linkage this conformation is indeed found (20,30).…”
Section: Coi$ornzational Analysissupporting
confidence: 80%
“…They demonstrated that these glycopeptides show certain distinct conformational features and that they are not completely flexible random coils. In a similar study of synthetic oligosaccharides of the type found in complex asparagine-linked glycopeptides, Bock et al 4 proposed that these branched oligosaccharides take on a rather extended conformation that contrasts with the partially folded conformations found for some of the high mannose chains. Bush et al 5 have used vacuum-uv CD to study a series of complex glycopeptidies, reaching conclusions that were consistent with those of Bock et al 4 Although glycopeptides of the O-linked or mucin type have been less intensively studied, Lemieux et al'j and Lemieux and Bock7 have used conformational energy calculations and NOE results to propose models for synthetic trisaccharide nonreducing terminal fragments of the blood group H-active oligosaccharides.…”
Section: Introductionmentioning
confidence: 96%